Effect of orchard management practices in high density of Apple cv. Mollies Delicious under temperate condition - KUMAR, MANOJ; JAMWAL, MAHITAL; KUMAR, VIJAY; CHARAK, AMIT; RAI, A. P. (Journal of Soil and Water Conservation, 2020)
An experiment was conducted during 2009-2011 to assess the effect of different treatments viz. Paddy straw mulch, forest soil mulch, black polythene mulch, bare basins, natural soil basins, frequent grass mowing of natural soil and its use in mulching, growing of mash in basins as cover crop and control on soil properties, fruit quality attributes and yield of Apple cv. Mollies Delicious. Different soil management practices were significantly increased the soil moisture status in soil. Forests soil at the rate of 20 kg per pit in the tree basins of Mollies Delicious tended to show the best results as there was highest soil moisture content (29.6%), N (147 kg ha-1), P (15 kg ha-1), K (234 kg ha-1), fruit weight (165.7 g), fruit size (72.65 Ã— 82.17 mm), yield (23.5 kg/ plant), TSS (18.70 %) and fruit firmness (10.8 kg) in the pools.